"If You Don't Grease a Palm, You'll Go Nowhere": The Lexical Representation of the Topic of Bribery in the Russian Language. Issue 6 (3rd June 2018) - Shchetinina, A.V.
Abstract : The article considers the problem of how a particular social lexicon related to the theme of bribery in Russia that was used in various linguistic contexts during various historical periods should be described. Such a study is needed due to the lack of a comprehensive description of the vocabulary of social relations, including institutional relations related to bribery [vzyatochnichestvo]. We show Russians have discussed this topic using words, idioms, non-idiomatic expressions, as well as proverbs. These lexemes reflect how native Russian speakers conceive of the social relations between citizens and members of the government. We discover 312 linguistic features that convey the seme "bribe" [vzyatka] and "bribery." These features define the semantic structure of words that make up the lexical-semantic field of "bribery." We develop an ideographic map that defines the structure and composition of this field. We have discovered that the semantic core of the field is the ideogram "custom of taking bribes" [obychay brat' vzyatki]. Its key lexical manifestation is the noun "bribery." We defend our interpretation of this phenomenon as a custom. We conduct an interpretative analysis of the contexts in which the lexical representations of this concept are used. On the basis of this analysis, we conclude that proverbs objectify the semantic components of the concept "custom, " including its identifying, regulatory, and other functions.